2007
DOI: 10.1021/ef0605495
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm for Determining Cylinder Pressure in Internal Combustion Engines

Abstract: In this paper, a genetic-algorithm- (GA-) based method has been developed to determine the instantaneous pressure in cylinders of internal combustion engines. Some parameters associated with a pressure curve in each cylinder are optimized from two validated submodels which reproduce the engine behavior using a genetic algorithm. In this process, the profile of both measured and modeled instantaneous angular speeds of the engine are compared. According to a typical design of a genetic algorithm, different opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…A first approach could be distributing the mean torque losses T fM between cylinders. On the other hand, for flexible crankshaft and driveline considerations (even for single-cylinder engines), there are several applications where an iterating procedure must be established, such as the indirect determination of in-cylinder pressure profile from the angular speed measurement [2,14,15]. Thus, the solution can be obtained by solving Eqs.…”
Section: Limits Of the Linear Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first approach could be distributing the mean torque losses T fM between cylinders. On the other hand, for flexible crankshaft and driveline considerations (even for single-cylinder engines), there are several applications where an iterating procedure must be established, such as the indirect determination of in-cylinder pressure profile from the angular speed measurement [2,14,15]. Thus, the solution can be obtained by solving Eqs.…”
Section: Limits Of the Linear Methodsmentioning
confidence: 99%
“…Second, for multi-cylinder engines, overlapping between torque profiles associated to the different cylinders makes it difficult to evaluate those coefficients. Finally, pressure acts as an unknown quantity when the inverse problem is applied; that is, pressure profile is determined from angular speed measurements by an indirect method [14,15]. In these conditions, a non-linear identification procedure is required.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [10], a GA based method has been developed to estimate the instantaneous pressure in cylinders. Some parameters associated with a pressure curve are optimized from two validated sub-models which reproduce the engine behavior via GA.…”
Section: Introductionmentioning
confidence: 99%
“…Although these relations are obvious, this study proposes a scientific methodology to evaluate their interactions. In a previous study, it was demonstrated that both terms φ and θ i (or θ j ) could be fairly well estimated by an indirect identification procedure (IMV). , Nevertheless, the third parameter (m p ) is directly related to the rest of terms, thus providing a good agreement with the pressure profile, but showing higher differences in relation with DM identification. It means that the number of input parameters initially considered as independent terms in the Wiebe’s function must be reduced, in order to ensure an adequate identification of this parameter.…”
Section: Resultsmentioning
confidence: 96%
“…To improve the exhaust emissions and performance of internal combustion engines, the influence of the design parameters over the engine behavior must be identified . Depending on the purpose (design, control, or diagnosis), pressure cycle measurements and modeling may be required. Among the different procedures to model the combustion process into a combustion chamber, the Wiebe’s parametric model that provides the mass burned fraction (MBF) corresponds to one of the most internationally extended . In this sense, many studies predict the correlations between some of the previous parameters. , …”
Section: Introductionmentioning
confidence: 99%